A pilot study demonstrating the feasibility of supermicrosurgical end-to-side anastomosis onto large recipient vessels in head and neck reconstruction. Issue 12 (December 2016) - Iida, Takuya; Yoshimatsu, Hidehiko; Yamamoto, Takumi; Koshima, Isao
Summary: In head and neck reconstruction using free flaps, microvascular anastomosis is commonly performed in an end-to-end fashion to relatively sizable arteries including the superficial temporal, facial, and superior thyroid arteries. With the recent developments of less invasive perforator flaps such as the superficial circumflex iliac artery perforator flap, anastomosis of smaller vessels of less than 0.8 mm diameter has become necessary; however, appropriate recipient arteries for end-to-end anastomosis are often absent. We have introduced supermicrosurgical end-to-side anastomosis to such arteries in 12 cases of head and neck reconstruction. Double-needle, short-thread microsutures were used to facilitate this procedure, and indocyanine green intraoperative angiography was used to confirm patency. All patients, except one with partial necrosis, survived. We believe that our method is a safe and reliable option for cases in which there is a discrepancy between the flap pedicle and recipient arteries.